2017
DOI: 10.3892/or.2017.5392
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rg5 treatment inhibits apoptosis of chondrocytes and degradation of cartilage matrix in a rat model of osteoarthritis

Abstract: Abstract. This study investigated the effect of ginsenoside-Rg5 on the degradation of articular cartilage in osteoarthritis rat model and on induction of chondrocyte apoptosis. Osteoarthritis rat model was prepared by ligament transection and medial meniscus resection. The rats were then treated with different doses (1, 2, 5, 10 and 15 µM) of ginsenoside-Rg5 for 48 h. The results from histopathological analysis revealed a significant (P=0.005) prevention of cartilage degradation in OA rat model by ginsenoside-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…In addition, Zhang investigated the effect of ginsenoside Rg5 (G-Rg5) on the degradation of articular cartilage in an OA rat model prepared by ligament transection and medial meniscus resection. Histopathological analysis showed that G-Rg5 significantly alleviated OA symptoms by preventing cartilage degradation, synovial membrane disintegration, and apoptotic cell death in the knee joints in ligament transection and medial meniscus resection OA rats [55]. An in vitro study revealed that G-Rg5 increased proteoglycan, collagen, and bone morphogenetic protein 2 levels and decreased MMP-13, IL-1β, TNF-α, nitric oxide, and inducible nitric oxide synthase levels in the chondrocytes of OA rats [55].…”
Section: Effects Of Ginseng and Ginsenosides In Rheumatic Diseasesmentioning
confidence: 97%
“…In addition, Zhang investigated the effect of ginsenoside Rg5 (G-Rg5) on the degradation of articular cartilage in an OA rat model prepared by ligament transection and medial meniscus resection. Histopathological analysis showed that G-Rg5 significantly alleviated OA symptoms by preventing cartilage degradation, synovial membrane disintegration, and apoptotic cell death in the knee joints in ligament transection and medial meniscus resection OA rats [55]. An in vitro study revealed that G-Rg5 increased proteoglycan, collagen, and bone morphogenetic protein 2 levels and decreased MMP-13, IL-1β, TNF-α, nitric oxide, and inducible nitric oxide synthase levels in the chondrocytes of OA rats [55].…”
Section: Effects Of Ginseng and Ginsenosides In Rheumatic Diseasesmentioning
confidence: 97%
“…In the process of OA development, matrix degradation and severe damage is often accompanied by excessive apoptosis of cartilage cells (20). Cell apoptosis, also known as programmed death, refers to the physiological process that nucleated cells trigger programmed cell death under the regulation of gene, which causes the natural death of cells and automatical removal of the non-functional, damaged and senescent cells (21). There is a small amount of apoptosis in the normal cartilage tissue, which is usually confined to the surface of cartilage tissue (22).…”
Section: Discussionmentioning
confidence: 99%
“…In OA chondrocytes, resveratrol may reverse the decrease in the levels of type II collagen, aggrecan, and glycosaminoglycan by regulating silent information regulator 2 type 1, hypoxia-inducible factor-2α, and MMPs expression [24,62,63,77]. Curcumin [28], naringin [42], icariin [16,78,79], berberine [68,69], sinomenine [72], tetramethylpyrazine [13,70,80], astragaloside IV [81], halofuginone [82], puerarin [83], quercetin [84], celastrol [54,85], harpagoside [32], ferulic acid [55], shikonin, acetylshikonin [86], ginsenoside Rb1 [76,87], cinnamophilin [30], honokiol [50], 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-d-glucoside [60], geniposide [31], ginsenoside Rg5 [74], cryptotanshinone [29], isofraxidin [33], paeonol [56], crocin [43], coptisine [44], piperine [45], butein [46], licochalcone A [36], tectorigenin [48], theaflavin-3,3′-digallate [59], anemonin [49], gastrodin [51], compound K…”
Section: The Effects Of Bioactive Components On Cartilage In Oamentioning
confidence: 99%
“…Paeonol alleviates chondrocyte apoptosis by regulating the levels of ROS, bcl-2, and bax [ 56 , 71 ]. Some components (icariin [ 9 ], sinomenine [ 72 ], astragaloside IV [ 73 ], quercetin [ 21 ], shikonin [ 35 ], tectorigenin [ 48 ], gastrodin [ 51 ], and ginsenoside Rg5 [ 74 ]) also exert anti-apoptotic effects on chondrocytes through various mechanisms. The promoting effects of puerarin [ 53 ], psoralen [ 75 ], magnoflorine [ 23 ], and emodin [ 38 ] on proliferation may be also beneficial to reverse cartilage apoptosis.…”
Section: The Anti-oa Activities Of Bioactive Components From Herbal Mmentioning
confidence: 99%
See 1 more Smart Citation